Dialect diversity and total factor productivity: Evidence from Chinese listed companies - Xiong, Jiacai; Chen, Linghong (Frontiers in Psychology, 2022)
Using a sample of Chinese listed companies over the 2007–2019 period, we examine the influence of dialect diversity on firm's total factor productivity. We find that the dialect diversity affects the psychological distance of interpersonal communication, and have a significant and negative impact on firm's total factor productivity. The results are robust to a battery of tests based on different specifications. The relationship between dialect diversity and firm's total factor productivity is more pronounced for state-owned enterprises, firms located in southern regions, and in firms with more capital-intensive. Furthermore, we demonstrate an innovation mechanism, a factor flow mechanism and a human capital accumulation mechanism through which dialect diversity inhibits total factor productivity. Overall, this paper provides new evidence and decision-making reference for coordinating the protection of dialect diversity and high-quality economic development.